Learning pathways for improving rehabilitation practices in the mining industry : two cases of coal mining and borrow pits - Mphinyane, Andani (Rhodes University, Faculty of Education, Department of Education, 2014)
This research investigates cases of learning pathways for improving rehabilitation practices for key occupations in the mining industry. The study is set up as a partnership research programme between Rhodes University Environmental Learning Research Centre in South Africa, and the South African Qualification Authority, focussing on workplace learning and sustainability practices. This research programme seeks to understand the implications of the move to a knowledge society, with its emphasis on knowledge building over time, particularly in and for the environmental sector. The research was conducted as a qualitative case study that made use of semi-structured interviews, document analysis, visual photographs and observations as instruments of data gathering. Participants were sampled from two case studies, one in Limpopo province and the other one in Mpumalanga Province, who are directly involved in rehabilitation practices and related education and training programmes. The study makes use of career stories from the key occupations to provide insight into workplace learning pathways to inform education and training in the mining industry. A series of analytical statements captures some of the main findings on early education histories, career choices, learning pathway decisions and experiences related to sustainable practices and some complexities related to learning pathways. Environment and sustainability education is a cross-cutting issue in the NQF; and it pertains to the mining sector, especially to rehabilitation practices, which form the focus of this study as little is known about learning pathways associated with these sustainability practices. Insights from the study should enable the sector to enhance rehabilitation training for key occupations and at the same time encourage lifelong learning contributing towards sustainable development.
Keywords: Coal mines and mining -- Environmental aspects -- South Africa; Environmental education -- South Africa; Sustainable development -- South Africa; Coal miners -- Education (Continuing education) -- South Africa; Borrow pits -- South Africa